TINJAUAN YURIDIS TINDAK PIDANA UJARAN KEBENCIAN PADA MEDIA SOSIAL TERHADAP PERILAKU CYBERBULLIYING MENURUT UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Anny Yuserlina; Failin failin (Ensiklopedia Education Review, 2022)
In today's modern era, the existence of various technological speeds ushers in changes and developments in the times, information technology science is also developing in accordance with modern times. Indonesia has been affected by the development of information technology in this era of globalization. One of the uses of this information technology is the existence of various social media spread to users in various circles. The crime of hate speech in positive law in Indonesia has been regulated in the Criminal Code which is further abbreviated as the Criminal Code, which is contained in Articles 156, 156a, 157, 310, 311 of the Criminal Code. Hate speech is also regulated in Law Number 11 of 2008 jo. Law 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions, namely in Article 28 Paragraph (2) jo Article 45 Paragraph (2). Hate speech and cyberbullying given to a certain person or group of people steal a lot of attention these days. Through posts on social media with hate speech, it is increasingly being discussed. Many internet users (netizens) disseminate a post (images, photos, videos, sounds, and words) using hate speech that causes insults, defamation, blasphemy, and so on.Keywords: Crime, Hate Speech, Social Media, Cyberbulliying